Phenomenology of dark radiation and string compactifications - Angus, S; Stephen Andrew Angus (2014)
In this Thesis I explore aspects of dark radiation and its role in String Phenomenology. Dark radiation is any additional hidden type of relativistic matter present in the Universe today, conventionally labelled as an "excess effective number of neutrino species", Δ Neff. It provides a powerful test of hitherto untested theoretical models based on fundamental theories such as String Theory. I begin by considering dark radiation in the LARGE Volume Scenario, a phenomenologically viable class of string compactifications. First I review how the minimal setup slightly overproduces axionic dark radiation via modulus decay. I then demonstrate that loop corrections to the main competing visible-sector decay process have a negligible effect and are unable to alleviate the tension with observations. In the following chapter I explore fibred extensions of the LARGE Volume Scenario. The predictions for Δ Neff are qualitatively different: in particular, models with a sequestered visible sector on D3 branes at a singularity are swamped by massless axions and decisively ruled out. I then consider TeV-scale supersymmetry in a model with anisotropic modulus stabilisation. If the Standard Model is realised on D7 branes wrapping the small volume cycle a hierarchy of soft terms is generated, which may have applications to natural supersymmetry. The final chapter takes a different approach and investigates the proposition that dark radiation, in the form of a Cosmic Axion Background, could explain the long-standing soft X-ray excess from galaxy clusters. I show for the Coma cluster that the morphology of the excess can be reproduced by axion-photon conversion in the intracluster magnetic field, provided the field is allowed to have more structure on smaller scales than typically assumed based on Faraday rotation data. This explanation requires an inverse axion-photon coupling M ∼ 1011 - 1012 GeV and a mean axion energy (ECAB) ∼ 50 - 250 eV.